PERANCANGAN USULAN PERBAIKAN PROSES PENGISIAN LIQUEFIED PETROLEUM GAS (LPG) TABUNG GAS 3 KG PADA SPBE PT X - Hermawati, Thalia
The Directorate of Metrology is a part of the ministry of domestic trade (MoDT) its primary duties include formulating, implementing and controlling policies, along with developing guidelines, norms, standards, procedures, and criteria, as well as providing technical guidance and evaluating policies implementation of metrology legal. Within the scope of its responsibilities which revolve around upholding the accuracy of measurements to serve border public interest, the metrology directorate has raised concerns regarding fluctuations in the volumetric contents of 3 kg LPG gas cylinders. To substantiate this concern of the metrology directorate, sample data were taken which were processed by calculating process stability using the proportion of defects that occurred in the filling process. The outcome of this analysis, it is found that there are 2 points, denoted as 10 and 13, exhibiting defect proportions that statistically, beyond to the upper control limit. This is such an indication that there is a problem that occurs in the gas-filling process. In response to this identified issue the metrology directorate endeavors to make improvements targeting the observed product defects that occur in the filling process of the 3 kg LPG gas cylinders. The method used to address this issue involved six sigma with the DMAIC (Define, Measure, Analyze, Improve, and Control) approach. In the define phase, knowing five critical factors that contributing to the occurrence of defects referred to as critical to quality (CTQ). The measure phase, the process’ sigma level is computed for the process filling of 3 kg LPG gas cylinders, yielding a value of 1.53. This level of sigma indicates that the filling process needs to be improved and that the level of sigma is still far from the desirable value of 6 sigma. The analyze phase, there are 18 factors that affect to defects subsequently guiding for formulating corrective solutions. The improve phase yields a set of proposed alternatives, including improvement to change the gross to net filling method to reduce defective products in the gas-filling process. This alternation results in an elevated sigma value 2.51, indicating defects reduction by decreasing 56.5% defect rate. The final phase, Control, a standard operating procedure (SOP) is designed to ensure that the improvements are implemented properly and to make it sustain over time.